2014
DOI: 10.17152/gefd.33332
|View full text |Cite
|
Sign up to set email alerts
|

Ulusal Fen Bilimleri ve Matematik Eğitimi Kongrelerindeki Fizik Eğitimi Çalışmalarının İçerik Analizi

Abstract: The purpose of this study is to examine and discuss published studies in the field of physics education in National Science and Mathematics Education Congress proceedings from 1994 to 2012. The research trends in these proceedings were analyzed through content analysis method. In line with the purpose, 282 studies were analyzed with a total of 735 studies in terms of demographic information of the authors (number, gender, institutions, etc.), general themes and physics topics, research types, sample size and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In our country, physics education research is conducted at universities locally and independent of each other; however, increase in physics education doctoral studies and financial support by government for research are parallel with US. The content analysis studies that have been carried out on graduate theses (Kaltakçı-Gürel et al, 2017a), articles published in peer-reviewed journals (Kaltakçı-Gürel et al, 2017b;Önder et al, 2014) and contributions in national congress (Kanlı et al, 2014) in the field of physics education in our country reveal this situation. However, although the increase in the number of government support and the increase in the number of researchers are 941 similar, in the world physics education is studied in the central research groups focusing on specific research topics, including researchers from different disciplines, while in our country, this situation continues interactively by collaborations of researchers at the relevant departments in the faculty of education.…”
Section: Insight Into Physics Education Research Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…In our country, physics education research is conducted at universities locally and independent of each other; however, increase in physics education doctoral studies and financial support by government for research are parallel with US. The content analysis studies that have been carried out on graduate theses (Kaltakçı-Gürel et al, 2017a), articles published in peer-reviewed journals (Kaltakçı-Gürel et al, 2017b;Önder et al, 2014) and contributions in national congress (Kanlı et al, 2014) in the field of physics education in our country reveal this situation. However, although the increase in the number of government support and the increase in the number of researchers are 941 similar, in the world physics education is studied in the central research groups focusing on specific research topics, including researchers from different disciplines, while in our country, this situation continues interactively by collaborations of researchers at the relevant departments in the faculty of education.…”
Section: Insight Into Physics Education Research Studiesmentioning
confidence: 94%
“…National and international content analysis studies in physics education (Kaltakçı-Gürel et al, 2017a;Kaltakçı-Gürel et al, 2017b;Kanlı et al, 2014;Önder et al, 2013) and science education (Chang, Chang, & Tsang, 2010;Lee, Wu, & Tsai, 2009;Tsai & Wen, 2005; Tzu-Chiang, Tzung-Jin, & Chin-Chung, 2014) make an important contribution to the literature by showing the gaps and shortcomings in the field. While Önder et al (2013) identified 'Learning approaches' and 'Misconceptions/learning difficulties' as the mostly studies themes by examining 46 physics education research articles in Journal of Turkish Science Education (TUSED) between the years 2004 and 2011 by content analysis, Kanlı et al (2014) found that the 'Nature of physics', 'Epistemology and Science literacy', 'Modeling' and 'Gifted education' were the least studied themes as a result of their content analysis study on 282 physics education studies presented and published in National Science and Mathematics Education Congress between the years 1994-2012. In international content analysis studies in science education (Chang et al, 2010;Lee et al, 2009;Tzu-Chiang et al, 2014) field, 'Conceptual change' and 'Conceptions / Misconceptions' were found to be the most featured themes, while 'Informal learning' and 'Educational technology' were the least studied themes.…”
Section: Conclusion: Transformation Of Physics Education Researchmentioning
confidence: 99%
“…Content analysis, which is the process of bringing together the results of scientific researches conducted in the same field separately from each other, combining them in a common denominator, categorizing them according to similar characteristics, and creating a systematic and accessible information source (Ültay, Dönmez Usta & Durmuş, 2017). By pointing out to the gaps and deficiencies, it has a guiding feature for researchers for future studies (Kanlı, Gülçiçek, Göksu, Önder, & Oktay, 2014). Descriptive content analysis is conducted in four stages.…”
Section: A Section Research Modelmentioning
confidence: 99%
“…Similarly, while one of the most fundamental factors for students to acquire these competencies is the teacher who teaches, the most important resource of a teacher is stated as textbooks (Yanık et al, 2017). Textbooks, which take their place from the smallest levels, should be arranged within the framework of curricula and in accordance with the standards of the countries that are at the top of the education level (Kanlı, 2004). In this context, studies in the literature examining mathematics textbooks from various aspects have been carried out (Arslan & Özpınar, 2009;Bingölbali & Bingölbali, 2020;Deringöl, 2020;Erşen et al, 2021;Gültekin, 2014;Karaaslan, 2019;Kayhan-Altay et al, 2020;Toptaş, 2010;Turan, 2019;Ubuz & Sarpkaya, 2014).…”
Section: Extended Abstract Introductionmentioning
confidence: 99%